Gen Z Muslims in Conducting Mate-Selection in West Sumatra - Indah Sari Rahmaini; Dwiyanti Hanandini; Jendrius Jendrius; Nitia Ayu (Jurnal Sosiologi Andalas, 2023)
This study aims to discover the subjective meanings of Gen Z Minangkabaus in West Sumatra in finding a mate and what popular cultural narratives produce these subjective meanings in the digital era. The method used in this research is to use a qualitative approach with a case study type. The data collection techniques used are observation and in-depth interviews. The data will be analyzed using the Miles and Huberman analysis techniques with codification, data presentation, and conclusion. The research will be analyzed using late-modernity studies from Ulrich Beck as a representation of society in the digital era and religion as a sacred canopy from Peter L Berger. Studies show that Gen Z Minangkabaus in West Sumatra still have an attachment to the family in finding a partner, such as paying attention to the origin of the partner's family